Prevalence and risk factors of overweight and obesity among urban school children in Elazig city, Eastern Turkey, 2007 - Pirincci, Edibe; Durmus, Birsen; Gundogdu, Cemal; Acik, Yasemin (Taylor & Francis Ltd, 2010)
Background: The prevalence of obesity is increasing dramatically all over the world. Very little data are currently available on the prevalence of childhood obesity in Turkey, and more research on the risk factors is required before preventive public health programmes can be put into practice. Aim: The aim of this study is to determine the prevalence of overweight and obesity and related factors in primary school students in Elazig, a city in eastern Turkey. Subjects and methods: In March-June 2007 a cross-sectional study of children aged 6-11 years old was performed. A total of 1782 girls and 1860 boys were observed. Weight and height were measured. Overweight and obesity using age- and sex-specific body mass index (BMI) cut-off points as defined by the International Obesity Taskforce were used. Results: Prevalence of overweight and obesity were 13.2% and 1.6%, respectively. According to gender, the prevalence of obesity in boys was 2.0% and overweight was 13.9%, while in girls, obesity was 1.2% and overweight was 12.5%. We found that overweight and obesity may be related to factors such as eating while watching television, and eating fast food. Conclusion: It was noted as a health problem that there are overweight students aged between 6 and 11 years attending primary schools in Elazig province.
Keywords: Prevalence; overweight; obesity; body mass index; children